Stakeholder Engagement Between KPSBU and dairy Farmers - Pradikto, Risky Adha; Rudito, Bambang (Journal of Business and Management, 2014)
A large number of people in rural Indonesia are depending on agriculture for their livelihood. But the development of Indonesian agriculture has not brought many benefits to these people, and has a little impact on rural poverty. In a developed and populous country such Indonesia, the problem of rural poverty cannot be resolved by redistribution of land that is in short supply. Dairy farming is an alternative that can be an answer from the problem above. But dairy farming needs further attention so this sector can grow. Besides, dairy farming is basically not deviate from local community customary habit. So, this occupation is easier to be implemented and developed. The growth chance of dairy farming sector in Indonesia is increasing when the cooperative system for dairy farming is introduced in some of rural area. In Lembang, there is a one of 5 biggest cooperative in Indonesia, it is Koperasi Peternak Susu Bandung Utara –namely KPSBU. The main product is dairy milk. KPSBU held many events, activities, and programs to stimulate the milk productivity of dairy farmers by increasing the members’ wealth which is the KPSBU’s main focus in their sustainability. The author conducted a qualitative research with ethnography approach by observation. This research is research on stakeholder engagement that conducted and conducting between the dairy farmers and KPSBU and comparing it with AA1000SES (2011). Key Words: Dairy Farmers, Cooperative, Engagement.